The Triassic climate and its evolutionary characteristics in Jiyuan area in south of North China Plate： Evidence from paleosol geochemistry - YANG Wentao; FENG Wanying; ZHANG Hongyu; WANG Min (河南理工大学学报. 自然科学版)
ObjectivesThe Triassic period was a period of rapid fluctuation of greenhouse climate， and the paleosol recorded abundant paleoclimate information. To study the climate change process from extreme to medium greenhouse，Methodsthe Triassic paleosoils in the Jiyuan area were selected as the research object to conduct principal element analysis to quantitatively estimate the annual average precipitation and temperature， and then reconstruct the paleclimate characteristics and evolution laws of the Triassic period.ResultsThe results showed that， （1）15 layers of paleosol （including calcareous soil， organic soil and gleyed soil） were identified in the Triassic strata in Jiyuan area. The quantitative paleoclimate reconstruction results show that the mean the meanannual precipitation in the Triassic period was 447~1 557 mm/a，and the temperature was 11~23 ℃. In the Early Triassic， the mean annual precipitation was 447~896 mm （with an increasing trend in precipitation in the late Early Triassic）， and the mean annual temperature was 16~23 ℃ （showing a downward trendin the Middle Triassic）， In the Middle Triassic， the mean annual precipitation was 679~1 539 mm/a showing a steady upward trend the mean annual temperature was 11~20 ℃. It dropped to its lowest point in the middle of the Middle Triassic. In the Late Triassic， the mean annual precipitation was 575~1 557 mm/a. There was less rainfall in the early and late stages of the Late Triassic， and the most rainfall in the middle stage， with temperatures ranging from 17~21 ℃， showing a good positive correlation with precipitation. （3） The climate fluctuations in the Triassic period of the North China Basin were relatively common， and the Early Triassic and early Middle Triassic were generally under a background of drought and heat， with a brief period of relative humidity. In the late Middle Triassic， rainfall increased significantly and began to shift towards a humid climate. In the Late Triassic， there was a significant fluctuation in rainfall， which was generally under a warm and humid background， accompanied by a relatively dry period.ConclusionsThe research results ccan provide reference for the study of the Triassic climate and its evolution laws.